Translating children’s literature: Additions as an aid to understanding irony - Haapakoski, Seija (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper analyses the translation of irony in children ’s literature. For children and adolescents irony is not only a matter of comprehension but also a matter of learning. However, to enjoy the literary device of irony one first has to get the point, one first has to understand the irony. Additions are discussed in this paper as a part of target text reader-oriented translation strategies. In the studied context, these strategies are regarded as tools to improve the interpretation and comprehension of irony by young target readers. Additions are discussed not merely as irony-building textual elements but also as parts of larger textual units. In the latter case, additions can provide extra information and this improves the ironic interpretation in its entirety. The results in this paper are based on a comparison of six translations (English, Finnish and Swedish as target languages) and the two source texts in German.